INOVASI PENDIDIKAN TINGGI DI ERA DISRUPSI: MENGEMBANGKAN KEBERMAKNAAN HIDUP MELALUI KECERDASAN SPIRITUAL: Innovation In Higher Education In The Era Of Disruptions: Developing The Meaningfulness Of Life Through Spiritual Intelligence - sodikin, sodikin (Piwulang: Jurnal Pendidikan Agama Islam, 2024)
ABSTRACK The meaning of life is an important aspect of mankind in the era of disruption. The current of globalization has made mankind lose the real meaning of his life. Modern man emphasizes material achievement and neglects spiritual needs. The purpose of this research is to explore the innovation of higher education in developing the meaning of life through spiritual intelligence that is the summit of human intelligence itself. This research uses a qualitative approach with a case study approach. Data is taken with in-depth interview techniques and observations. The main informants in this study are the nurses and all the managers who are involved in the management of the training. Data analysis is carried out in three stages: condensation, display, and verification. The results of this study show that spiritual intelligence is very closely related to the meaning of human life. People who have spiritual intelligence have spiritual consideration in making decisions. It's different from emotional intelligence which emphasizes more on responding to the human needs of both individuals and groups. Spiritual intelligence drives one to have self-awareness, empathy, compassion, gratitude, forgiveness, and a sense of interconnection with others and the universe. The era of disruption keeps mankind alive in anxiety and uncertainty. There are several strategies that can be implemented to develop the meaning of life through the development of spiritual intelligence, namely (1) integrating spiritual and emotional intelligence into the curriculum, (2) integrating mindfulness and personality rituals into the educational system, (3) instilling the sense and significance of life in learning. Makna hidup merupakan aspek penting bagi manusia di era disrupsi. Arus globalisasi telah membuat manusia kehilangan makna hidup yang sesungguhnya. Manusia modern lebih menekankan pencapaian materi dan mengabaikan kebutuhan spiritual. Tujuan dari penelitian ini adalah untuk mengeksplorasi inovasi perguruan tinggi dalam mengembangkan makna hidup melalui kecerdasan spiritual yang merupakan puncak dari kecerdasan manusia itu sendiri. Penelitian ini menggunakan pendekatan kualitatif dengan pendekatan studi kasus. Data diambil dengan teknik wawancara mendalam dan observasi. Informan utama dalam penelitian ini adalah para perawat dan seluruh pengelola yang terlibat dalam pengelolaan pelatihan. Analisis data dilakukan dalam tiga tahap: kondensasi, display, dan verifikasi. Hasil penelitian ini menunjukkan bahwa kecerdasan spiritual sangat erat kaitannya dengan makna hidup manusia. Orang yang memiliki kecerdasan spiritual memiliki pertimbangan spiritual dalam mengambil keputusan. Berbeda dengan kecerdasan emosional yang lebih menekankan pada respon terhadap kebutuhan manusia baik individu maupun kelompok. Kecerdasan spiritual mendorong seseorang untuk memiliki kesadaran diri, empati, kasih sayang, rasa syukur, pemaaf, dan rasa keterkaitan dengan orang lain dan alam semesta. Era disrupsi membuat manusia hidup dalam kegelisahan dan ketidakpastian. Ada beberapa strategi yang dapat dilakukan untuk mengembangkan makna hidup melalui pengembangan kecerdasan spiritual, yaitu (1) mengintegrasikan kecerdasan spiritual dan emosional ke dalam kurikulum, (2) mengintegrasikan ritual kesadaran dan kepribadian ke dalam sistem pendidikan, (3) menanamkan rasa dan makna hidup dalam pembelajaran.